If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4a + -3 = 63 Reorder the terms: -3 + -4a = 63 Solving -3 + -4a = 63 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4a = 63 + 3 Combine like terms: -3 + 3 = 0 0 + -4a = 63 + 3 -4a = 63 + 3 Combine like terms: 63 + 3 = 66 -4a = 66 Divide each side by '-4'. a = -16.5 Simplifying a = -16.5
| -3x-17=27-7x | | 5x^2+13x=-6 | | 2x+4+x^2+2x+4+x^2=p | | 3x+2x=2+4x-5 | | 5v+8=-7+8v | | 4x+3(x-20)=402 | | 62=-73+9x | | 1-x=0 | | 8(n+6)=88 | | 2x^2=2x | | 5+y=0 | | -10v+2=-138 | | b/4=3 | | 10c=100 | | 8(x-5)-2(3x+4)=5x-6 | | a-61=20 | | 96-v=21 | | f+30=50 | | 3x^2=y | | 103=59+x | | 13z=26 | | (a+6)9= | | -5x-2y=9 | | -(3-5)= | | 4(p-2)=p+4 | | 10x-15=40 | | (x+2)2x=70 | | 4p-3=3p+8 | | 2x^6-16x^2=0 | | 2x^2-18x+27=0 | | 4x-7=11+y | | 2p+2=12 |